(untitled) (Economic studies journal, 2019)
The study aims at finding out the impact of organizational justice (interactional justice- distributive justice) on organizational commitment among employees in Wahda Bank in Sirte. The researcher relied on the analytical descriptive approach using the questionnaire as a tool for data collection .the questionnaire was distributed to all employees totaled (48). (37) of which were returned and all of them were chosen for the statistical analysis. The study showed many results ,including that there was a medium degree of exercise of distributive justice and interactional justice ,also the level of employees commitment was medium. The results also indicate that there was a significant correlation between organizational justice and organizational commitment . The results of the study indicated that there was an impact of interactional justice on organizational commitment by (62%), and no impact for distributive justice on organizational commitment . The main recommendations of the study was the need to adopt some management procedures to strengthen organizational justice to impact on employees’ behavior and commitment. Another essential recommendations was to raise the level of organizational commitment of employees through the development of training programs for the improvement of managers skills and there way to deal with employees at Wahda bank.